Do Field Dependence-Independence Differences of Game Players Affect Performance and Behaviour in Cultural Heritage Games? - Raptis, George E.; Fidas, Christos A.; Avouris, Nikolaos M. (Proceedings of the 2016 Annual Symposium on Computer-Human Interaction in Play - CHI PLAY '16, 2016)
Stimulated by a large number of different theories on human cognitive processing, suggesting that individuals have different habitual approaches in retrieving, recalling, processing and storing information, this paper investigates the effect of field dependence/independence with regards to game players' performance in the context of a cultural heritage game. Thirty two participants took part in an in-lab study and were classified as field dependent or independent based on a cognitive style elicitation instrument. Quantitative analysis methods were used to examine gaming performance in terms of game completion time, information seeking and items collection. The results revealed statistically significant differences in task completion time and in crucial information retrieval situations. Findings are expected to provide useful insights for practitioners and researchers with the aim to design more user--centric cultural heritage games.